The Principle of Subrogation in Motor Vehicle Loss Insurance in South Barito Regency - Simanjuntak, Manat; Wijaya, Andika; Januardy, Ivans (Dinasti Research, 2025)
This study aims to analyze the implementation of the principle of subrogation in motor vehicle loss insurance in South Barito Regency, focusing on the challenges faced and the solutions that can be taken to ensure the effectiveness of the principle. The research uses an empirical research method by collecting data through in-depth interviews, observations, and documentation studies. The data were analyzed in a qualitative descriptive manner to provide a comprehensive picture of the phenomenon being studied. The results of the study show that the application of the principle of subrogation often faces obstacles, such as the lack of transparency of the insured, the low public understanding of insurance law, and the culture of peaceful settlement between the insured and third parties. In addition, the relatively small claim value compared to operational costs is also a consideration for insurance companies not to continue the subrogation right. This study recommends strengthening regulations, increasing education to the public, and utilizing technology to support the implementation of the subrogation principle more optimally.